The Effectiveness of Psychoeducation Based Behavior Modification in Improving School Well-Being among Elementary School Students in Semarang City - Wening Wihartati; Ari Yuniastuti; Irwan Budiono; Yuni Wijayanti (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: This study aims to test the effectiveness of the “RELAKS” psychoeducation program, which is based on behavior modification and combines relaxation techniques, self-efficacy, and assertive behavior reinforcement to improve the school well-being of elementary school students. Methods: The study uses a quantitative experimental method with a pre-test and post-test control group design. The study subjects consisted of 50 students, including 25 experimental group students from SD Bringin 01 and 25 control group students from SD Bringin 02 in Semarang City. The research instrument used the school well-being scale questionnaire. Data analysis was conducted using the Independent Sample T-Test and Paired Sample T-Test. Results: The primary outcome was the improvement of school well-being scores. The results showed significant differences (p < 0.05) across all dimensions of school well-being between the experimental and control groups, indicating the positive effect of the intervention. Furthermore, a significant increase (p < 0.05) was observed in the experimental group's scores from pre-test to post-test, confirming the effectiveness of the “RELAKS” program. The Psychoeducation program improved school well-being scores across all dimensions. In the experimental group, the Being score rose from 30.32±3.26 to 36.72±3.29 with an average difference of 6.40, falling within the 95% CI range of 5.51–7.29. The Loving dimension increased by 5.04 points (95% CI 3.22–6.86), Health increased by 4.84 points (95% CI 4.80–5.35) and Having dimension, the increase reached 2.48 points (95% CI 0.79–4.16). The effect size indicates a moderate to large category, especially in the Being dimension, which reflects the strongest impact of the intervention. Conclusion: In conclusion, our study demonstrates that the psychoeducation program effectively improves school well-being among elementary school students by integrating behavior modification techniques. This research offers valuable insights for developing supportive educational interventions.